Studi Parkir Kampus Anggrek Kondisi Eksisting dan Penambahan Lahan Parkir Baru Terhadap Pengguna Kampus Anggrek Binus University - Hidayat, Irpan; Makmur, Amelia; Juliastuti, Godeliva (ComTech: Computer, Mathematics and Engineering Applications, 2011)
A parking area is built in a building to facilitate vehicle users of the building. Based on this, Binus University planned to build parking area in its several campus. One interesting issue to explore is the parking capacity at Anggrek Campus. The purpose of this study was to determine the saturation levels of parking for the existing condition compared to the addition of new parking area. To perform analysis turnover parking calculation is used . Based on research results the number of cars entering Anggrek campus was greater than the volume of available parking at the campus (turnover = 1.58), so there was a lot of trouble to find a parking space that makes parking users find alternative parking spaces such as parking area 52). However, since the 8th floor parking area functioned, the turnover rate reduced to 0.54 which indicates that there was a saturation level decrease of 65%.